Optimizing the Use of Social Media YouTube and Instagram in Learning Syari’ah Economic Law - Nur Ikchsan; Siti Kholifah; Fajar Hari Prasetyo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze effective strategies in optimizing the use of social media, especially the YouTube and Instagram platforms, by students of Syari’ah business law courses. The focus of the research is to identify students' efforts to use social media as a relevant and useful tool in the context of social media business from an Islamic perspective and legal protection issues related to existing YouTube and Instagram social media content. The research method used is qualitative, with strategic analysis through surveys, interviews and observations of Syari’ah business students, especially content owners (Youtubers) and users who actively use YouTube as a medium for uploading content. , Content created by YouTubers is considered copyrighted. The data obtained was then analyzed to explore and document aspects of the Kedungsapur area that were thoroughly researched. The results of this research provide detailed insight into optimizing social media use of Syari’ah business law students by uncovering unintentional mentions and attributions to certain parties throughout the public domain. This can lead to defamation, which is prohibited in Islam and violates the ITE Law, Islam emphasizes the importance of conveying information accurately and not manipulating or misusing facts. Further findings show that the presence of hackers has an impact on how content creators protect YouTube and Instagram. The meaning of this research can contribute to the development of innovative learning strategies and deepen students' understanding of the application of the law Syari’ah trading in the digital era.